Preparation, characterization, and thermal and photo degradation of polypropylene/oil palm leaves fiber composite - Khayat, Huwayda (2014)
The fast increase in world population dramatically increases the need of packaging materials. Synthetic polymers are expensive, nonabrasive and nonrenewable materials. The increase usage of these materials has originated an issue of solid waste disposal. The accumulation of plastic waste in landfills is becoming a hazard for the environment, and ultimately for human. Therefore reduction of the uses of synthetic polymers especially for the above mentioned applications should be given priority. Polypropylene (PP) is normally tough, flexible and suitable to be used in different applications such as packaging, labeling and textiles. While oil palm leaf fiber (OPLF) found to be good filler for thermoplastic polymer composites. In this study the use of OPLF as a reinforcement material for PP composites, and their mechanical and thermal properties, were investigated. Effects of Epolene E-43 as a compatibilizing agent for the composites on their mechanical, thermal properties and morphology were assessed. Moreover, the effect of iron (III) chlorides on the thermal and photo-oxidative degradation of the composites was also examined via thermogravimetric analysis (TGA) and UV-irradiation study of the doped PP/OPLF composites. OPLF was extracted from dried-oil palm leaf (OPL) and the composite sheet was formed by melt blending technique using internal mixer machines and compression molding. Composites of 10, 20, 30, 40, 50 and 60% by weight of OPLF were prepared. The addition of Epolene-43 as compatibilizer improves the overall properties of PP/OPLF composites. The composite with 20w% fiber loading possess the best mechanical and chemical properties. Increase in fiber loading, in the compatibilized and uncompatibilized composites, reduces the tensile strength and elongation at break. However, it increases in tensile modulus, flexural strength and modulus of the composites. Water absorption increases with the increase of fiber loading by 10, 13, 15% for 40, 50 and 60w% fiber loading, but the addition of Epolene E-43 reduces water absorption. Interaction between the components of the composite is only physically as indicated by Fourier Transform infrared spectroscopy (FTIR) results except for 20w% fiber content. The addition of Epolene E-43 forms new ester bonds between the components of the composites. It was observed from differential scanning calorimetric (DSC) data that the degree of crystallinity reduces by 44% and 36% for both 50w% of modified and unmodified fiber content composites, respectively, with the increase of OPLF content. Thermo gravimetric analysis (TGA) results indicate that the PP/OPLF composites are more stable than the PP. Meanwhile dynamic mechanical analysis (DMA) shows that the presence of the OPLF enhances mobility but reduces the stiffness. Addition of iron (III) chloride accelerates thermal and photo degradation of PP/OPLF composites. Epolene E-43 is a good compatilizer as it reduces the composite void size and number as shown by field emission scanning electron microscopy (FESEM) micrographs indicating its addition improve interaction of OPLF and PP matrix.